Evaluation of different internal diameter coated modulation columns within the context of solid‐state modulation. Issue 9 (5th March 2021) - Giocastro, Barbara; Zoccali, Mariosimone; Tranchida, Peter Q.; Mondello, Luigi
Abstract: The solid‐state‐modulator is a consumable‐free thermal modulator, used within the context of comprehensive two‐dimensional gas chromatography. Its consumable‐free nature is guaranteed by the presence of a thermal‐electric cooler device located between two heated chambers, everything located outside the gas chrpmatograph oven. The aim of the present research is to evaluate the solid‐state‐modulator modulation performance in relationship to different modulation capillary geometries. For this purpose, two coated modulation capillaries with the same length, but with different internal diameters (0.25 and 0.18 mm) were used. The effects of gas linear velocity, modulator temperature, and modulation period were evaluated in several applications involving standard alkanes and a sample of diesel fuel. Fundamental gas chromatography parameters (peaks widths, resolution) were measured under the different experimental conditions. Detailed information is provided on gas flow optimization, with particular emphasis on the efficiency of chromatography band reinjection onto the second‐dimension column. The results obtained from the present investigation highlight how the modulation capillary characteristics have a great impact on the overall comprehensive two‐dimensional gas chromatography separation. Specifically, considering the results herein attained, the use of a 0.18 mm ID × 0.18 μm df modulation column is advisable compared to a 0.25 mm ID × 0.25 μm df one.